Fog Computing: A Conceptual and Practical Overview (International Journal of Innovative Research in Computer Science & Technology, 2021)
Electronic gadgets, appliances, medical  equipment, cameras, sensors, and cars are all part of the  Internet of Things (IoT), which enables smart cities and infrastructure. It is predicted based on evidences that a  minimum of forty nine billion IoT devices shall definitely be  linked or connected with the Internet by or before 2020.  Those devices will generate a huge and unprecedented  amount of information, which conventional systems and  cloud systems may find challenging to handle. Fog  computing was created to address the shortcomings of  existing technologies. Fog offers storage, computation, data,  and application services at the network's edge, comparable to  cloud computing. This article discusses the features that  generally makes fog or edge computing a good stage for the  recently evolved technology “IoT”, as well as application,  characterization and interrelated research in the trending  fields including IoT and Fog. Edge computing is a suitable  platform for IoT because of its heterogeneous nature,  mobility support, very low latency, and huge number of  nodes. Rather of transmitting data to the cloud, data will be  processed at the network edge.
Keywords: Cloud Computing; Edge computing; Fog; Fog computing; Internet of Things